Investigations on the influence of Moringa oleifera on the growth, haematology, immunity and disease resistance in Oreochromis niloticus with special reference to the analysis of antioxidant activities by PAGE electrophoresis. (26th May 2021) - Elgendy, Mamdouh Y.; Awad, Elham S.; Darwish, Doaa A.; Ibrahim, Taghreed B.; Soliman, Waleed S. E.; Kenawy, Amany M.; Abumourad, Iman M. K.; Abbas, Hossam H.; Abbas, Wafaa T.
Abstract: The study aimed to evaluate the effect of dietary inclusions of Moringa oleifera on the growth, haematology, antioxidant activities, immunity, and protection against Aeromonas hydrophila in Oreochromis niloticus . Diets supplemented with 0.5% or 1% of either crude moringa (CM) powder or alcoholic moringa extracts (AME) were used. Weight gain (WG), specific growth rate (SGR), and haematological parameters (RBCs count, Hb content and HCT %) were significantly improved ( p  < 0.05) with feeding CM than control fish, meanwhile they decreased significantly ( p  < 0.05) in AME treatments. The feeding of CM significantly improved WBCs and lymphocyte counts ( p  < 0.05). Cholesterol and triglycerides showed no significant changes ( p  > 0.05) in CM treatments, but they significantly increased in fish fed 0.5% AME. Liver and kidney functions (ALT, AST, uric acid and creatinine) were not relatively affected by moringa treatments. The non‐specific immune responses of fish fed CM showed significant ( p  < 0.05) improvement, including serum proteins, lysozyme activity, and antiprotease activity. Peroxidase activity (POX) and Cytochrome P450 (CYP) were increased significantly ( p  ˂ 0.05) with CM and in 0.5% AME treatment. Superoxide dismutase (SOD) and Catalase (CAT) showed insignificant changes ( p  > 0.05). Antioxidant activities were also analysed by staining on polyacrylamide gel electrophoresis. Challenge experiment indicated higher survivability of fish fed moringa‐supplemented diets. The survivability was found the highest (80%) in the group fed with 0.5% CM. These results indicate that dietary supplementation with crude M . oleifera enhances the growth, antioxidant activities, immune competence and potentiates resistance against A . hydrophila in O . niloticus, with the greatest effects of 0.5% crude M . oleifera .